Research Progress on Zearalenone Biodegradation and Its Detoxification Mechanism - LI Kailong, LIU Kunlun, XIN Ying, YANG Chenxian, WANG Zikun (Shipin Kexue)
Mycotoxins are a class of contaminants that pose serious harm to the safety of grains, food and animal feed, causing massive resource waste and severe economic loss. Zearalenone (ZEN) has been detected at high rates in moldy corn, wheat, and other grains, and exposure to ZEN pollution can induce reproductive, hepatic, and renal toxicity. Due to its widespread contamination and severe hazards, ZEN has become a major hidden danger to food safety. When traditional physical and chemical methods are used to degrade ZEN, there is a risk of secondary pollution. Therefore, food-related industries are always seeking biodegradation technologies with higher specificity, targeting capacity, safety, and adaptability. In this paper, the toxicity and harm of ZEN, microorganisms and enzymes that degrade ZEN, and the application of modern biotechnology in the removal of ZEN are reviewed with particular emphasis on the types of biodegradation products and the detoxification mechanism of ZEN, and potential directions for the application of ZEN are pointed out so as to provide a theoretical basis for further studies on biological detoxification of ZEN.